Kinerja Bagian Tata Pemerintahan Dalam Tugas Evaluasi Dan Monitoring Pada Kantor Kelurahan Di Kota Manado - Nila Pratiwi; Agustinus B. Pati; Fanley Pangemanan (Sam Ratulangi University, 2022)
This study aims to analyze the performance of the governance section in carrying out evaluation and monitoring tasks at the village office in Manado City. The method used in this study is a qualitative method with a descriptive study that aims to describe, summarize various conditions, various situations, or various social reality phenomena that exist in the lives of the people who are the object of research. The sample used in this study amounted to 5 people with a sampling technique that is purposive sampling. Data collection was done by means of interviews which were analyzed using qualitative techniques, which resulted in descriptive data. This descriptive data can be in the form of speech or writing and behavior observed by people whose information is extracted through in-depth interviews and categorized then together with information obtained through library searches to sharpen the analysis of the trend of findings in research. The results of this study indicate that the evaluation and monitoring program that has been carried out by the Administration of the Regional Secretariat of the City of Manado has a very positive effect on the Kelurahan offices in the City of Manado.